Literasi al-Qur’an di Era Digital: Analisis Bibliometrik dan Kajian Tren Penelitian di Indonesia 2018-2024 - Amri Saputra; Maesaroh Maesaroh; Muhammad Farij Al-Kahfi; Havid Nur Solikhin; Dwi Ratnasari; Ansorul Alim (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to analyze the development of scientific literature on Qur’anic literacy in the digital era in Indonesia during the period 2018–2024 using a bibliometric approach. A total of 16 scientific documents were retrieved from the Scopus database and analyzed using RStudio with the Bibliometrix package and the Biblioshiny interface. The results reveal that research on digital Qur’anic literacy in Indonesia has shown an increasing trend, although the number of publications remains limited. The dominant topics include Islamic education, the use of digital media in Qur’anic learning, and the dynamics of Islam in Indonesian society. Moreover, the level of collaboration among authors and institutions is largely national, with limited international contributions. These findings suggest that Qur’anic literacy in the digital era is not merely an adaptation to technological advancement but also a form of recontextualization of Islamic values within the modern digital environment. This study provides a foundational perspective for developing technology-based Qur’anic education models that maintain the authenticity of Islamic teachings while remaining relevant to the needs of the digital generation.